Cost management in public higher education institutions in Malaysia: Challenges in financial sustainability - Siraj, Siti Alawiah; Nik Ahmad, Nik Nazli; Ismail, Suhaiza (Faculty of Economics and Management Universiti Kebangsaan Malaysia, 2016)
The paper seeks to examine senior academic and administrative officers’ perceptions on important cost management practices which should be implemented in Malaysian public higher education institutions (Public universities) to help reduce the operating costs of public universities given the current environment of substantial cuts in budgetary allocations. A mail questionnaire survey was undertaken with the bursars, deans and directors of the twenty public universities in Malaysia to examine the respondents’ perceptions on various cost management practices that may be useful in reducing the operating costs of public universities and ensure longer-term financial sustainability of these institutions. The survey also examined respondents’ perceptions on long term strategies which should be implemented to close budget gaps and areas and activities which may have been affected by budgetary reductions. Findings of the survey suggest that respondents feel that a number of different cost management strategies may be effective in assisting public universities to achieve financial sustainability and reduce dependence on government funding. The findings of the survey have important practice and policy implications for the governance of public universities in an era of reduced budgetary allocations and increased scrutiny on the financial management of public sector organisations in general and Public universities in particular.